A systems approach to implementation of personalized cancer therapy - Mills, Gordon B. (Henry Stewart Talks, 2017)
Targeted therapy for cancer, Adaptive resistance: PI3K pathway, Tumor heterogeneity, Challenges & need for functional genomics, Identification of PIK3R1 driver mutations, Human proteomics atlas: reverse phase protein array (RPPA), Checkpoint inhibition as potential targets, Synergy, operating model & strategy for combination therapies